2016
DOI: 10.1016/j.sleh.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a sleep health promotion program for college students

Abstract: Objectives We conducted a pilot study of a sleep health promotion program for college students. The aims of the study were to 1) determine the feasibility of the program, and 2) explore changes in sleep knowledge and sleep diary parameters. Design Open trial of a sleep health promotion program for college students. Setting A small liberal arts university in southwestern Pennsylvania Participants University students (primarily female). Intervention Active intervention components included individualized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 60 publications
3
36
0
1
Order By: Relevance
“…Sleep hygiene education, cognitive behavioral therapy (CBT), relaxation, mindfulness, and hypnotherapy are effective strategies to improve sleep among higher education students [ 105 , 106 , 107 ]; thus, universities should consider incorporating these strategies to improve sleep quality of these students. One systematic review indicated increased effectiveness of CBT compared to other interventions in improving sleep quality and duration [ 107 ], and another systematic review showed that online CBT for insomnia is effective in improving sleep quality and duration among adults with chronic insomnia by identifying and modifying factors that contribute to poor sleep, including stress [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep hygiene education, cognitive behavioral therapy (CBT), relaxation, mindfulness, and hypnotherapy are effective strategies to improve sleep among higher education students [ 105 , 106 , 107 ]; thus, universities should consider incorporating these strategies to improve sleep quality of these students. One systematic review indicated increased effectiveness of CBT compared to other interventions in improving sleep quality and duration [ 107 ], and another systematic review showed that online CBT for insomnia is effective in improving sleep quality and duration among adults with chronic insomnia by identifying and modifying factors that contribute to poor sleep, including stress [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of strategies can be adopted by universities to improve students’ sleep, including sleep hygiene education [ 122 , 123 ], cognitive behavioral therapy for insomnia (CBTi), relaxation, mindfulness and hypnotherapy [ 124 ]. CBTi is an intervention that involves cognitive, behavioral and educational interventions [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this category, 5 articles were included,[ 18 19 20 21 22 ] which correspond to 55% of the number of articles analyzed. From this perspective, it was perceived that health education is a cross-cutting aspect to all interventions, being considered one of the main pillars for HP in higher education institutions and above all, for student protagonism either as a leader of interventions or as a multiplier.…”
Section: Methodsmentioning
confidence: 99%